Improving the thermophysical properties of hybrid nanocellulose-copper (II) oxide (CNC-CuO) as a lubricant additives: A novel nanolubricant for tribology application - Mohd Kamal, Kamarulzaman; Sakinah, Hisham; Kadirgama, Kumaran; Devarajan, Ramasamy; Samykano, Mahendran; Saidur, R.; Yusaf, Talal (Elsevier, 2023)
The primary objective of the present analysis is to investigate the thermophysical properties of hybrid nanocellulose and copper (II) oxide nanoparticles added to engine oil as a lubricant for piston ring-cylinder liner application. Kinematic viscosity, viscosity index (VI) and dynamic viscosity have been performed for measurement of properties at varying temperatures (ranging from 30 °C to 90 °C) and different concentrations (ranging from 0.1 % to 0.9 % volume concentration). Thermal characteristics have been measured using similar temperatures and concentrations to determine thermal conductivity and specific heat capacity. In the results, as the concentration of the CNC-CuO nanoparticle increases, the VI also increases. This proves the combination of CNC-CuO particles with engine oil improves the lubricity of the base oil concerning its viscosity by 44.3 %-47.12 %. The lowest and highest improvements in the dynamic viscosity were 1.34 % and 74.81 %. The highest increment of thermal conductivity ratio for the selected nanolubricant was 1.80566 % in the solid concentration of 0.1 % at 90 °C. The specific heat capacity of nanolubricant tends to reduce slightly with an increase in temperature. Overall, the addition of CNC-CuO nanoparticle in the engine improved thermophysical properties behaviour's performance at 0.5 % concentration. The results can benefit the heat transfer application, especially tribological.